Translation and validation of the Malay version of the Emotion Regulation Questionnaire for Children and Adolescents ERQ-CA - Mohd Ali, Manisah; Mohd Hoesni, Suzana; Rosharudin, Nur Afrina; Yusoff, Siti Rashidah; Ihsan Razman, Mohamad Omar; Khairuddin, Khairul Farhah; Mohd Daud, Tuti Iryani; Muhammad, Noor Azimah; Puad Mohd Kari, Dharatun Nissa (MDPI, 2022)
The Emotion Regulation Questionnaire for Children and Adolescents (ERQ-CA) has been translated and adapted globally. This study aimed to examine the psychometric properties of the Malay version of the ERQ-CA. The ERQ-CA underwent forward and back translation twice and was tested in two separate studies, Study 1 and Study 2, with 296 and 359 students aged between 13 and 14 years old, respectively. Cronbach’s alpha values were calculated, and confirmatory factor analysis was conducted. The results from Study 1 demonstrate good internal consistency for cognitive reappraisal and expressive suppression. The results indicate a good factor loading for most of the items, but only one value of the goodness-of-fit met the criteria for a good fit. The results from Study 2 show improvements in the values of the goodness-of-fit that are comparable to previous studies, but there was a decrease in the factor loading scores. Overall, the Malay version of the ERQ-CA possesses acceptable reliability and validity. Further studies are required in the near future to develop a Malay version of the ERQ-CA that reasonably represents Malaysian adolescents.